Constitutionalism, libertarianism, and Conflict with despotism in the thought of Dehkhoda - Reza Afsordeh; Hamed Ameri Golestani; Lena Abdolkhani; Hamed Mohagheghnia (پژوهش‌های تاریخی ایران و اسلام, 2020)
Dehkhoda is one of Iran's most influential literary political elites in the constitutional era. He has dealt with the most important political issues of Iran's constitution in the course of many years, with a powerful pen and a penetrating view. Among the literate and the cultural, at least, there was at least one person who was as knowledgeable as the Dehkhoda who knew the status quo in both thought and action. Understanding his important political ideas, beyond his literary and cultural personality, plays an important role in the proper understanding of constitutionalism. He was a full-fledged "progressive" who had a national and Iranian view of the important feature of his valuable vocabulary. On the basis of this rise, he regarded constitutionalism as a positive, legal, libertarian political system, and in the negative sense defined it as an antithesis of "despotism". Dehkhoda must be regarded as a continuation of the early intellectuals of the Qajar era, who go beyond them and move towards a different understanding and understanding. This article seeks to explain Dehkhoda's understanding of constitutionalism, given her place in modern Iranian intellectual history.